2019
DOI: 10.3390/f10080700
|View full text |Cite
|
Sign up to set email alerts
|

3-D Reconstruction of an Urban Landscape to Assess the Influence of Vegetation in the Radiative Budget

Abstract: Increased urbanization and climate change have resulted in the intensification of the urban heat island (UHI) effect, particularly in tropical cities. One of the main causes of UHI is the man-made urban surfaces influencing the radiation budget by absorbing, reflecting, and emitting radiation at various wavelengths. The radiative budget of a city is directly influenced by the urban geometry, surface materials, direct solar radiation and incident angle, and atmospheric diffuse radiation. Vegetation cover, in co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(22 citation statements)
references
References 30 publications
0
21
0
1
Order By: Relevance
“…The inversion procedure proposed in this work can be potentially used for a wide range of experiment applications if only broadband BOA irradiance is available. Indeed, direct and diffuse BOA irradiance in narrow bands are commonly required for many urban and vegetation studies (Dissegna et al 2019). This is typically the case for studying the sun induced chlorophyll fluorescence (Gastellu-Etchegorry et al 2017).…”
Section: Discussionmentioning
confidence: 99%
“…The inversion procedure proposed in this work can be potentially used for a wide range of experiment applications if only broadband BOA irradiance is available. Indeed, direct and diffuse BOA irradiance in narrow bands are commonly required for many urban and vegetation studies (Dissegna et al 2019). This is typically the case for studying the sun induced chlorophyll fluorescence (Gastellu-Etchegorry et al 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Singapore include maps of ecosystem cover (Gaw et al, 2019), topography (Dissegna et al, 2019), vegetation height (Dissegna et al, 2019), leaf area index (LAI) (Richards and Wang, 2020), building locations and heights (Dissegna et al, 2019), the locations of publicly accessible nature spaces (Richards et al, 2020a), and the road network (OpenStreetMap, 2020).…”
Section: Current Urban Characteristics Of Tengah and Comparison Townsmentioning
confidence: 99%
“…gov.sg archive (Singstat, 2016). Building data were taken from a dataset originally sourced from OpenStreetMap (OpenStreetMap, 2020), but with additional digitization to include all buildings in Singapore in approximately 2017 (Dissegna et al, 2019). This dataset also included the height of all buildings, by cross-referencing with a high resolution digital surface model (Dissegna et al, 2019).…”
Section: Current Urban Characteristics Of Tengah and Comparison Townsmentioning
confidence: 99%
See 1 more Smart Citation
“…Vegetation covers 56% of the total land area (Yee et al, 2011). The evapotranspiration's cooling effect and shade provided by trees have been widely investigated in Singapore, even by some coauthors of Mughal et al (2019), who have concluded that trees cannot be ignored to assess the local climate (Dissegna et al, 2019; Liu et al, 2017). However, in this study, Mughal et al did not consider the presence of trees.…”
Section: What About Evapotranspiration and Tree Shade?mentioning
confidence: 99%